Estimation of the error of the simplified algorithm of processing of functions of deflations of deformed frames of bodies of rolling stock - Horobets, Yevhen (Technology audit and production reserves, 2021)
The study is aimed at assessing the size of the error that arises when processing the results of examining the geometric characteristics of the bearing structures of rolling stock units using an algorithm without using trigonometric functions. The object of the research is a method of simplified alignment of the deflection function of body frame beams to the horizontal plane. One of the biggest problem areas is the lack of understanding by some customers of the work of the possibility of using this algorithm due to the lack of information about the errors that arise in the simplified calculation. The study was carried out by comparing the results of processing the initial data by two methods, obtained during the work on the inspection of the state of the supporting structures of the unit of the shunting diesel locomotive TGM6. One method, the algorithm of which is the subject of this study, assumes that no complex calculations are used during data processing. The second method involves the use of an algorithm for aligning the deflection functions of the body frame beams of a rolling stock unit of railways in the horizontal plane, taking into account all trigonometry tools, which will exclude the accompanying calculation errors of the simplified method. After processing the initial data, two sets of results were obtained – with the desired calculation error and without. Comparison of these datasets yielded an error value for frame tilt of 5.7. For clarity, the size of the error was compared with the expanded uncertainty values of the main sources of uncertainty in the methodology for examining the bearing structures of rolling stock. On the basis of the analysis of two methods of leveling the inclination to the horizontal plane of the deformed rolling stock body frame, the expediency of such an approach has been proved. The results obtained make it possible to reasonably use the Simplified approach to processing the data obtained during the survey of the geometric characteristics of the rolling stock. If necessary, the developed mathematical model can be used to improve the accuracy of calculating the uncertainty of measurements of geometric characteristics, as well as for use in the study of modification of existing or development of new measurement techniques